Worker absenteeism in search equilibrium - Per Engström; Bertil Holmlund (Institute for the Study of Labor (IZA), 2007)
The paper presents a general equilibrium model of search unemployment that incorporates absence from work as a distinct labor force state. Absenteeism is driven by random shocks to the value of leisure that are private information to the workers. Firms maximize profits while recognizing that the compensation package may affect the queue of job applicants and the absence rate. The analysis provides results concerning the effects of social insurance benefits and other determinants of workers' and firms' behavior. The normative anlysis identifies externalities associated with firm-provided sick pay and examines the welfare implications of alternative policies.
Keywords: 330; Fehlzeit; Friktionelle Arbeitslosigkeit; Sozialversicherung; Lohnfortzahlung; Zeitallokation; Personalzusatzkosten; Leistungsmotivation; Arbeitsangebot